Pelayanan Publik dalam Perspektif Islam: Landasan, Prinsip, dan Implementasi di Era Kontemporer - Nur Wahidillah; Shifa Rosa Apriyani; Vanessa Ria Meilani; Zahwa Mutia Ashari (Kajian Administrasi Publik dan ilmu Komunikasi, 2025)
Public service in the Islamic perspective is a comprehensive concept, integrating religious principles with governance practices to achieve justice, efficiency, and public welfare. This concept is based on the Qur'an and Hadith, which emphasize values ​​such as justice (*'Adl*), responsibility (accountability), consultation (*Shura*), and welfare (*Maslahah*). Public service in Islam is not only a transaction, but also has moral and spiritual aspects, where providing the best service is considered as worship and a form of obedience to Allah. The scope of public service in Islam includes various important sectors such as education, health, law, and socio-economic welfare. Islamic history, especially in the era of the Prophet Muhammad SAW and the Khulafaur Rasyidin, shows concrete examples of the application of these principles, such as the construction of mosques as centers of learning, the establishment of hospitals, and the management of Baitul Mal for the fair distribution of resources. In the modern context, especially in Indonesia, Islamic values ​​have proven to play an important role in bureaucratic reform and improving the quality of public services. Despite facing obstacles such as lack of resources and integration between institutions, the application of Islamic principles in public services—as seen in Islamic hospitals and Islamic travel agents—shows the possibility of producing more just, humane, and quality services. Thus, the Islamic approach to public services provides an ethical framework that is flexible, responsive, and focused on the welfare of society.